Challenges of Vietnam’s higher education in the context of Industrial Revolution 4.0 - Phong, Nguyen Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
The Industrial Revolution 4.0 is bringing radical changes in all fields, directly affecting the number and kinds of future jobs on a global scale as well as the role and function of knowledge expoitation of universities in the society. Universities, from the perspective of being the cradle providing the largest and most qualified human resource of society, especially in the field of creative entrepreneurship, is facing enormous and necessary challenges. Hence, there is an urgent need for universities to dramatically change their activities to adapt to the future society, helping students have high employment opportunities. With the function of leading the society, discovering and exploiting knowledge, the role of universities in IR 4.0 becomes more and more important and faces new challenges. The research reviews literature and analyses the impact of IR 4.0 on the basic functions of a university: training, research and knowledge exploitation, thereby drawing and analyzing the challenges faced by universities in the next few decades. The research also gives some suggestions, ideas for innovating university activities to adapt and overcome these challenges. Code: <span style="text-align: left; color: #000000; text-transform: none; text-indent: 0px; letter-spacing: normal; font-variant: normal; font-weight: 400; text-decoration: none; word-spacing: 0px; white-space: normal; orphans: 2; -webkit-text-stroke-width: 0px; background-color: #ffffff;">20092901